Ковалець Т. «Litwie z Koroną spólna sprawa…». Облога запорожцями Гомеля та козацько-литовські переговори у червні 1651 року за матеріалами маловідомих документів (публікація джерел) // Науковий вісник Чернівецького національного університету імені Юрія Федьковича: Історія. Чернівці, 2021. Вип. 1. С. 151-158. - Kovalets, Taras (My University, 2021)
The article has archeographic nature and contains the text of two documents in Polish found in the Manuscripts Department of the Vasyl Stefanyk Lviv National Scientific Library, the report of a certain apprentice of the nobleman Krzysztof Fasz about the siege of Gomel and the report prepared for the command of the crown army about Cossack diplomatic mission to the field hetman of Lithuania Janusz Radziwill in June 1651. The purpose of the article is the first edition and scientifically comment on the mentioned documents together with their translation into Ukrainian. The year 1651 promised to be a turning point for the young Cossack state, which was trying to establish itself on the map of Europe. At the end of the winter, the Zaporozhian Army, the Crimean Khanate, the Polish Crown, and the Grand Duchy of Lithuania began preparations for a new round of armed conflict. The war, as two years before, was to last on two fronts – the Cossack-Polish and the Cossack-Lithuanian. Cossack regiments led by Martyn Nebaba, Matviy Gladky and Prokop Shumeyko, as well as certain Tatar units were transferred to Lyubech and Loyev. The Cossacks guarded the crossings across the Dnipro and Sozh, preparing for the possible arrival of Lithuanian troops or the beginning of the Cossack offensive to the north. In the spring, Sivershchyna, which was a border region, became the scene of small skirmishes between the Cossacks of the Chernihiv Regiment and some units of the Lithuanian army. These skirmishes quickly escalated into full-fledged hostilities. Finally, on May 26th, the Cossacks began the siege of Gomel Castle. Although the course of the siege of Gomel has been well studied by M. Hrushevsky, the published document (№ 1) contains valuable and unique evidence of the activities of the Cossack departures, the mood in the besieged castle and the mention of the massacre of the burghers made by the Lithuanian garrison, also movement of the main Lithuanian army to repel Gomel. The second document, a report from the Lithuanian camp about the Cossack embassy to J. Radziwill, is already known to researchers. For the first time, M. Hrushevsky partially introduced it into scientific circulation, using several fragments of it translated into Ukrainian. However, the historian did not pay much attention to the interesting data given in this report, first of all those concerning the description of the reception of envoys, their life in the Lithuanian camp, etc. Also, the researcher failed to correctly read certain fragments, including the name of one of the Cossack envoys.
Keywords: Військо Запорозьке, Януш Радзивілл, Стефан Пободайло, Мартин Небаба, кампанія 1651 р., Гомель, дипломатія